2021
DOI: 10.1073/pnas.2020293118
|View full text |Cite
|
Sign up to set email alerts
|

Impaired inhibitory GABAergic synaptic transmission and transcription studied in single neurons by Patch-seq in Huntington’s disease

Abstract: Transcriptional dysregulation in Huntington’s disease (HD) causes functional deficits in striatal neurons. Here, we performed Patch-sequencing (Patch-seq) in an in vitro HD model to investigate the effects of mutant Huntingtin (Htt) on synaptic transmission and gene transcription in single striatal neurons. We found that expression of mutant Htt decreased the synaptic output of striatal neurons in a cell autonomous fashion and identified a number of genes whose dysregulation was correlated with physiological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…However, whether these inclusions are the real cause of the pathology has been the subject of intense debate, and it is clear that mHTT can also be toxic independently of the formation of large aggregates (reviewed in [1]). Regardless of whether it forms inclusions, mHTT has been shown to drive multiple cellular alterations in aspects such as mRNA transcription [13][14][15], protein degradation and post-translational modifications [16], synaptic function and plasticity [17][18][19][20][21] and mitochondrial activity [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether these inclusions are the real cause of the pathology has been the subject of intense debate, and it is clear that mHTT can also be toxic independently of the formation of large aggregates (reviewed in [1]). Regardless of whether it forms inclusions, mHTT has been shown to drive multiple cellular alterations in aspects such as mRNA transcription [13][14][15], protein degradation and post-translational modifications [16], synaptic function and plasticity [17][18][19][20][21] and mitochondrial activity [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The mean number of detectable genes per cell was 3247 ± 193 in Pyr ←LP neurons and 4013 ± 189 in Pyr ←ORBvl neurons (Supplementary Data 8 – 10 ). We initially assessed the specificity of our sampling for the two neuron types based on the expression levels of a set of known markers 48 , 55 . As expected, we found that both Pyr ←LP and Pyr ←ORBvl neurons expressed pan-neuronal genes, such as Snap25 (synaptosome-associated protein 25), and excitatory neuron genes, such as Slc17a7 (vesicular glutamate transporter 1) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The latter techniques have proven instrumental in detecting genes responsible for vulnerability in both post-mortem brain tissue of human patients and animal models of disease 58,59 . Patch-seq has been used previously in this context to study pancreatic β-cells in a model of type-2 diabetes 60 , in an in vitro model of schizophrenia 61 , and in a model of corticospinal tract degeneration 62 , all of which returned potential mechanistic targets of physiological dysfunction, but this technique has not been previously used in brain sections from a preclinical disease model (including those for Alzheimer’s or other neurodegenerative diseases).…”
Section: Resultsmentioning
confidence: 99%